(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
Real estate analysis in the developing cities of Central Siberia is a hot topic in the modern world of real estate. This paper discusses the main directions of development of the real estate market in the cities of the region: Omsk, Krasnoyarsk, Novosibirsk, Irkutsk, etc. The possibility of improving housing conditions in developing cities of Central Siberia, analyzing the situation on the housing market, developing a model for improving housing conditions.